2020
DOI: 10.5114/aoms.2020.98401
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 disease: novel clinical manifestations and therapeutic exploration

Abstract: Introduction: This study aims to provide further clarifications on some new clinical characteristics of COVID-19 recently discovered by our research group. Material and methods: In this single-centred, retrospective study, we collected all confirmed cases of COVID-19 diagnosed in Dazhou, Sichuan, China from January 23 to February 25, 2020. All the cases were either imported from Wuhan or transmitted in family clusters. We analysed general information on all patients. Meanwhile, the contents of lactic acid, Fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
0
7
1
Order By: Relevance
“…We found that factors associated with the development of new in-hospital neurologic events seem to be mostly related to disease severity, both in respiratory parameters (PaO 2 /FiO 2 ratio, ARDS severity, and chest CT findings) and inflammatory markers (C-reactive protein, D-dimer, and neutrophil index/lymphocyte). Interestingly, headache on admission remained a factor associated with this outcome in the multivariate analysis; however, the frequency of headache in our study was higher than in other studies [ 16 19 , 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 95%
“…We found that factors associated with the development of new in-hospital neurologic events seem to be mostly related to disease severity, both in respiratory parameters (PaO 2 /FiO 2 ratio, ARDS severity, and chest CT findings) and inflammatory markers (C-reactive protein, D-dimer, and neutrophil index/lymphocyte). Interestingly, headache on admission remained a factor associated with this outcome in the multivariate analysis; however, the frequency of headache in our study was higher than in other studies [ 16 19 , 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Patients with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may develop COVID-19, which has caused more than 1 million deaths worldwide to date [7]. Risk factors associated with death may vary between countries with different ethnical backgrounds [8][9][10][11][12][13][14][15]. These risk factors have been poorly described in Latin America, which represents a barrier to establishing proper epidemiological and clinical decisions to reduce the toll caused by this worrisome pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Lopinavir/ritonavir and remdesivir are among the drugs with poor lung distributions, and thus are considered to be inadequate for the inhibition of SARS-CoV-2 [59,60].…”
Section: Mostafa Ghaneimentioning
confidence: 99%